High performance supercapacitors using lignin based electrospun carbon nanofiber electrodes in ionic liquid electrolytes. (11th February 2019) - Perera Jayawickramage, Rangana A; Ferraris, John P
Abstract: Flexible, free standing and binder-free electrodes were fabricated by electrospinning from a series of lignin: polyvinyl alcohol (PVA) polymer blends, followed by heat treatment. PVA has the dual function of facilitating the electrospinning of lignin and acting as a sacrificial polymer. Upon stabilization, carbonization and CO2 activation, carbon nanofibers (ACNF) derived from the lignin:PVA 80:20 blend displayed a high surface area of 2170 m 2 g −1 and a mesopore volume of 0.365 cm 3 g −1 . ACNFs derived from all the compositions show high degrees of graphitization based on Raman analysis. Pyr14 TFSI ionic liquid (IL), modified by mixing with propylene carbonate and ethylene carbonate to reduce the viscosity and increase the ionic conductivity, was used as a high-performance electrolyte. The resulting IL mixture exhibited a four-fold increase in ionic conductivity compared to the neat IL Coin cell supercapacitors using electrodes derived from lignin:PVA 80:20 blends and this electrolyte displayed 87 F g −1 specific capacitance and 38 Wh kg −1 energy density which is the highest reported energy density for lignin:PVA blends to date.